2014
DOI: 10.1002/ejp.514
|View full text |Cite
|
Sign up to set email alerts
|

Pain threshold and sleep quality in women with endometriosis

Abstract: Sleep quality was poorer and the pain threshold at certain body sites was lower in the group of women with endometriosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(25 citation statements)
references
References 30 publications
2
19
0
4
Order By: Relevance
“…Pain threshold was lower in pain patients with endometriosis [71] as well as with juvenile idiopathic arthritis [72]. Furthermore, pain threshold correlates with functional scores in osteoarthritis patients [73].…”
Section: Discussionmentioning
confidence: 96%
“…Pain threshold was lower in pain patients with endometriosis [71] as well as with juvenile idiopathic arthritis [72]. Furthermore, pain threshold correlates with functional scores in osteoarthritis patients [73].…”
Section: Discussionmentioning
confidence: 96%
“…Visceral hypersensitivity testing also revealed lower pain thresholds among women with endometriosis in a rectal balloon dilation test 18 and lower pain thresholds and larger pain areas were reported in women with symptomatic endometriosis after an intramuscular saline injection into the hand 4 . In a more recent study concerning pressure-pain thresholds at 20 different body sites, with use of the visual analog scale, it was reported that there was a lower pain threshold in the greater trochanter and abdomen in fertile-aged women with endometriosis compared with controls 24 . A population-based study carried out by Slater et al, with similar musculoskeletal pain response testing as in the present study, showed decreased pain thresholds in women experiencing severe menstrual pain 29 .…”
Section: Discussionmentioning
confidence: 99%
“…Only recently, a study [ 31 ] evaluated the role of PA in women diagnosed with endometriosis. Though it focused on sleep quality and pain threshold, Nunes et al [ 31 ] considered that performing PA regularly can contribute toward relieving sleep disorders and consequently may improve the quality of sleep; therefore, patients with endometriosis should be encouraged to exercise during treatment. Even if it considers PA in women with endometriosis, this study just addresses a general effect on women's well being, rather than the role of regular exercise in relieving pelvic pain and affecting the disease course.…”
Section: Discussionmentioning
confidence: 99%